Curriculum and the production of indigenous subjects - Adir Casaro Nascimento; Antonio Hilario Aguilera Urquiza (Universidade Estadual de Maringá, 2015)
The policy on school education has always been explicit in its intentions to produce identities for indigenous peoples. The Federal Constitution of 1988 broke with the assimilationist/integrationist/colonizing proposal of curricula imposed on indigenous people and recognizes the ethnic identities of indigenous people inserted within the context of their cultural relations and the right to their customs, values, traditions, languages and knowledge. The use of the mother tongue and of learning processes has been orienting categories in the curricula of their schools. With culture as the focal point of discussion, this text is supported on testimonies by indigenous teachers from Terena, Guarani and Kaiowá tribes, subjects living the ambiguities and conflicts as well as their identities and the identities of those looking for schooling in different communities. Despite the difficulties that the indigenous school still faces, indigenous movements question homogenous and colonizing schooling models. This school is part of their lives and plays its social role of working with knowledge without excluding cultures as producers of sense and meaning, their knowledge that guarantees the difference in curriculum, area of struggle, and in the production of indigenous subjects.